Retorika Retorika dalam Debat Calon Presiden Indonesia 2024: Debat - Eka Putri Saptari Wulan; Rosmilan Pulungan; Dairi Sapta Rindu Simanjuntak; Dedy Rahmad Sitinjak (Universitas Asahan, 2025)
Rhetoric plays a strategic role in political discourse, particularly in presidential debates that serve as a public arena for shaping candidate image and influencing voter perception. This study aims to analyze rhetorical devices employed by the three Indonesian presidential candidates during the 2024 election debates. Utilizing a descriptive qualitative approach, the data were sourced from official debate transcripts retrieved from the YouTube channel of the Indonesian General Elections Commission (KPU RI). Data collection was conducted through observation and documentation, followed by content analysis to interpret the rhetorical patterns used by each candidate. The findings reveal that all three candidates employed a variety of rhetorical devices, including alliteration, anaphora, hyperbole, metaphor, parallelism, and personification. Anies Baswedan frequently used metonymy and rhetorical questions; Ganjar Pranowo prominently employed metaphors and personification; while Prabowo Subianto heavily relied on parallelism and metaphors. These findings suggest that rhetorical devices were strategically utilized to reinforce arguments, enhance credibility, and shape public perception throughout the political campaign.